Teaching character and virtue in schools - Arthur, James, 1957-; Kristján Kristjánsson (Professor of education); Harrison, Tom, 1976-; Sanderse, Wouter; Wright, Daniel (Daniel Francis), 1973- (Citizenship, character and values education, 2017)
"Teaching Character and Virtue in Schools addresses the contemporary issues of quantification and measurement in educational settings. The authors draw on the research of the Jubilee Centre at the University of Birmingham in order to investigate the concern that the conventional wisdom, sound judgement and professional discretion of teachers is being diminished and control mistakenly given over to administrators, policymakers and inspectors which in turn is negatively effecting pupils' character development. The books calls for subject competence to be complemented by practical wisdom and good character in teaching staff. It posits that the constituent virtues of good character can be learned and taught, that education is an intrinsically moral enterprise and that character education should be intentional, organised and reflective. The book draws on the Jubilee Centre's expertise in support of its claims and successfully integrates the fields of educational studies, psychology, sociology, philosophy and theology in its examination of contemporary educational practices and their wider effect on society as a whole. It offers sample lessons as well as a framework for character education in schools. The book encourages the view that character education is about helping students grasp what is ethically important and how to act for the right reasons so that they can become more autonomous and reflective individuals within the framework of a democratic society. Particularly interested readers will be educational leaders, teachers, those undertaking research in the field of education as well as policy analysts with a keen interest in developing the character and good sense of learners today"--Publisher's description